Prognosis and Risk Factors of Radiation-Induced Lymphopenia in Early-Stage Lung Cancer Treated With Stereotactic Body Radiation Therapy - Zhao, Qianqian; Li, Tingting; Chen, Gang; Zeng, Zhaochong; He, Jian (Frontiers in Oncology, 2020)
Background: To investigate the role of stereotactic body RT (SBRT) in decreased total peripheral lymphocyte counts (TLCs) in patients with early stage lung cancer and explored possible risk factors for RT-induced lymphopenia. Materials and Methods: We analyzed the TLCs and lymphocyte subsets of 76 patients in our prospective clinical database who received SBRT for early stage lung cancer treatment. Relationships between clinical factors or dosimetric parameters and TLCs were evaluated using Spearman’s correlation analysis and Chi-square tests for continuous and categorical variables, respectively. Multivariate linear regression analysis was used to control for confounding factors. Kaplan-Meier analysis with a log-rank test and a multivariate Cox regression model were used for survival analysis. Results: Most patients (64/76, 84.2%) experienced decreased absolute lymphocyte counts following SBRT, as well as shifts in lymphocyte subset distributions. Spearman’s correlation coefficients between post-SBRT TLCs and the percentage of lung and heart receiving 5 to 50 Gy (in 5 Gy increments) shown that most lung DVH parameters [V(10)-V(50)] significantly negatively correlated with post-SBRT TLCs, while only heart V(5), V(20), V(25), V(30), and V(45) were significant. Univariate analyses revealed that lower Pre-SBRT TLCs level, higher mean lung dose, longer treatment duration and longer TBT were significantly associated with a lower level of Post-SBRT TLCs (all P < 0.05). Stepwise multivariate linear regression, which incorporated all significantly clinical variables and SBRT-related parameters in univariate analysis, revealed that lower pre-SBRT TLCs (P < 0.001), higher heart V5 (P = 0.002), and longer total beam-on time (TBT) (P = 0.001) were the independent risk factors of decreasing in post-SBRT TLCs. Patients with lower post-SBRT TLCs and longer TBT exhibited significantly inferior progression-free survival (P < 0.001 and P = 0.013) and overall survival (P = 0.006 and P = 0.043). Conclusions: G2 and more severe lymphopenia after SBRT might be an independent prognostic factor for poorer outcome in early stage lung cancer. Lowering heart V5 and TBT may spare circulating lymphocytes in designing SBRT plans and have the potential to further improve survival outcomes.